Automatic Retractable Cloth Drying System - Ishak, Nurul Najwa; Mohd Shah, Nor Shahidah; Zainal, Mohd Shamian; Mohamad, Mahathir; Ab. Rahman, Munirah (Progress in Engineering Application and Technology, 2020)
Nowadays, most people spend less time at home. Thus, an automatic cloth drying system is convenient for our daily routine. In this project, a cloth drying system, that can retrieve-in hanging clothes automatically when it is raining and then, retrieve-out out again when the sun is shining, is developed. The system is controlled by an Arduino UNO and applied two sensors, a rain sensor and an LDR to detect rain and sunlight, respectively. The project involved a conversion of electrical power into mechanical power for the movement of the retractable cloth drying system using a power window motor. This system can withstand until 5 kg of wet clothes.